Nazi race ideologues. (19th October 2016) - Stone, Dan
ABSTRACT: Stone argues that we need to disaggregate Nazi race ideologues since they do not form one undifferentiated mass. Ultimately, all the Nazis were race ideologues and chief among them were Hitler, Himmler and the other leading figures. All of the leading Nazis, whether they dealt specifically with 'racial policy' or not, put forward a racialized ideology, but those who made a name for themselves specifically as race theorists did not therefore all share the same views, nor did they all contribute in equal measure to the regime's crimes. Nor did race science, however deeply it threw its lot in with Nazism, drive the regime as much as did a kind of racial mysticism, or 'thinking with the blood'. Here Stone suggests how we might evaluate the relative contributions made to the development of the Third Reich and its crimes by race scientists of different stripes, on the one hand, and theorists of racial-political conspiracies on the other.